Pemanfaatan Artificial Intelligence Sebagai Media Pembelajaran Pada Era Pendidikan 4.0 - Adam, Samsudin Hi; Ali, Silvani Umar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The conscious use of AI by teachers has increased their creativity in improving the quality of education. With the continued development of artificial intelligence technology, it is hoped that AI can make a greater contribution to improving the quality of human life and solving various complex problems in various fields (Lukman, 2019). This article discusses the use of AI as a learning medium. It is hoped that this article can be a reference for teachers in utilizing AI in learning. This study uses a library research approach. Library research is research conducted by collecting data and information from various library sources, such as books, journals, articles, and other documents that are relevant to the topic being studied. AI has great potential in transforming education by providing a more personalized learning experience, increasing administrative efficiency, and expanding access to quality education. With the right strategy, AI can be an effective tool in improving the quality of education globally. The presence of AI technology is a breakthrough in the field of educational technology to facilitate learning. The use of technology wisely and in a controlled manner can trigger educational acceleration. The use of artificial intelligence AI in learning and assessment in the digital era has a significant impact on educational transformation.